2001
DOI: 10.1002/1521-3951(200103)224:2<515::aid-pssb515>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of InAs Quantum Dots on Silicon

Abstract: We present a comprehensive investigation of molecular beam epitaxial (MBE) grown InAs quantum dots (QD) on silicon (001) and (111) by reflection high energy electron diffraction (RHEED) and Raman spectroscopy in UHV environment and ex-situ by atomic force microscopy (AFM) and transmission electron microscopy (TEM). Two different ways were developed to prepare up to 10 11 cm --2 InAs QDs on Si(001). One is the conventional mode by exceeding a critical thickness of deposition at which 2D growth changes towards a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…One opening shows a successfully grown nanowire while in the adjacent opening, an InAs cluster is observed that did not develop into a nanowire. Those clusters are typically below 40 nm in diameter and about 10 nm in height, in agreement with the observations from InAs quantum dot growth on Si [22,23]. The dimensions were determined from atomic force microscopy (AFM) measurements as shown in the inset of Fig.…”
Section: Nucleation and Growthsupporting
confidence: 83%
See 1 more Smart Citation
“…One opening shows a successfully grown nanowire while in the adjacent opening, an InAs cluster is observed that did not develop into a nanowire. Those clusters are typically below 40 nm in diameter and about 10 nm in height, in agreement with the observations from InAs quantum dot growth on Si [22,23]. The dimensions were determined from atomic force microscopy (AFM) measurements as shown in the inset of Fig.…”
Section: Nucleation and Growthsupporting
confidence: 83%
“…2 (B). These results indicate that nanowire growth starts out from an initial nucleation site consisting of an InAs island on the As-terminated surface [22][23][24], and not from an In particle. clusters that form under reduced In flows do not form top /111S facets, which impedes nanowire growth.…”
Section: Nucleation and Growthmentioning
confidence: 80%
“…However, an attempt of InAs‐QD‐growth on Si, for in‐stance, has to take into account the lattice mismatch of ∼11% between InAs and Si, which is even larger than that of ∼7% between InAs and GaAs. As a matter of fact, the direction of research on the formation of InAs QDs on Si substrate has been along the modification of the original (001) substrate: either by applying the process of pre‐treatment such as hydrogen passivation 7, 8 or by using a 2 o ‐tilting of the substrate 9. Nevertheless, one can find a number of reports on this subject in the literature including the high‐resolution transmission‐electron‐microscopy investigation of Si/InAs nanoislands/Si structure 10, photoluminescence study of band offset for InAs QDs in a Si matrix 11, morphologic study of InAs nanoislands on Si using scanning tunneling microscopy 12, comparison of selective growth of InAs nanoislands on nanopatterned SiO 2 /Si and bare Si 13, atomic‐force‐microscopy (AFM) study of the temperature‐, or InAs coverage‐dependent morphology of InAs islands on (1 × 1) (001) Si 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…grown on GaAs substrates [17][18][19][20]. In contrast, little attention has been paid to achieving InAs QDs on Si substrates [21,22], although it is of great importance to integrate InAs QDs into current Si technology, which ultimately reduces the cost and enhances their optoelectronic properties. Since there is a large lattice mismatch (∼11.5%) between InAs (a = 6.058 Å) and Si (a = 5.431 Å) 5 , it is a great challenge to grow epitaxial InAs QDs on Si.…”
Section: Introductionmentioning
confidence: 99%